Obsessive-Compulsive Disorder During the COVID-19 Pandemic—A Systematic Review - Linde, Elisabeth S.; Varga, Tibor V.; Clotworthy, Amy (Frontiers in Psychiatry, 2022)
Background: The COVID-19 pandemic and its associated restrictions may contribute to a deterioration in mental health; individuals with obsessive-compulsive disorder (OCD) may be particularly affected. This systematic review aimed to investigate the effects of the current pandemic on people diagnosed with OCD, and whether pandemics may affect the development of OCD symptoms. Methods: We conducted a systematic search using NCBI PubMed, SCOPUS, and Google Scholar on February 9, 2021. Research articles related to OCD and COVID-19 or other pandemics were attempted to be identified using pre-defined search terms. Case reports, clinical guidelines, letters, and clinical research articles including ≥100 participants were included; reviews were excluded. The systematic review adheres to PRISMA guidelines and the Newcastle-Ottawa Scale was used to assess the quality of the included clinical research articles. Results: A total of 79 papers were included in the full-text assessment. Of these, 59 were clinical research articles, two were clinical guidelines, six were case reports, and twelve were letters. The research articles examined OCD symptoms in adult patients with diagnosed OCD, the general population, pregnant women, healthcare workers, students, and young adults, children, and adolescents. Only one study on OCD in previous pandemics was identified. Conclusion: This systematic review found that people both with and without diagnosed OCD prior to the pandemic generally experienced a worsened landscape of symptoms of OCD during the COVID-19 pandemic. However, the responses are heterogeneous and many factors other than the pandemic seemed to affect the development of OCD symptoms. To prevent the impairment of symptoms and the development of new cases, close monitoring of patients with OCD, and education of the general public is essential. Literature is still limited; thus, multinational, and cross-cultural, longitudinal studies are warranted to gain further insights on this topic.